2017
DOI: 10.1016/j.tate.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations between teaching-related motivations and student-reported teaching quality

Abstract: Teaching-related motivations are often assumed to influence teaching quality; however, the empirical evidence regarding the directionality of such influences is scarce. The present study thus examined the reciprocal links between teaching-related motivations (selfefficacy and enthusiasm for teaching) and student-reported teaching quality (classroom management, learning support, and cognitive activation). Two-level cross-lagged panel analyses across three time points (with an initial sample of 165 secondary-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 61 publications
4
39
1
12
Order By: Relevance
“…In sum, this study clarified our theoretical and empirical understanding of the causal order and nature of the associations between self-efficacy and the dimensions of burnout (exhaustion and disengagement) in teachers. Specifically, our study findings contribute to previous study findings and arguments (Holzberger et al, 2013;Praetorius et al, 2017) that TSE should not necessarily be examined as an antecedent variable but as a consequential variable. Understanding the causal order of teacher-relevant constructs will help us not only in developing richer theory but also correctly implementing strategies to assist our teachers in their professional lives.…”
Section: Resultssupporting
confidence: 81%
“…In sum, this study clarified our theoretical and empirical understanding of the causal order and nature of the associations between self-efficacy and the dimensions of burnout (exhaustion and disengagement) in teachers. Specifically, our study findings contribute to previous study findings and arguments (Holzberger et al, 2013;Praetorius et al, 2017) that TSE should not necessarily be examined as an antecedent variable but as a consequential variable. Understanding the causal order of teacher-relevant constructs will help us not only in developing richer theory but also correctly implementing strategies to assist our teachers in their professional lives.…”
Section: Resultssupporting
confidence: 81%
“…That is, dimensions of instructional quality predicted TSE rather than the other way around. Finally, in Praetorius et al's (2017) study, based on longitudinal data from both teachers and students, revealed no significant cross-lagged effects between TSE and teaching quality when teachers' stable characteristics were taken into account. Moreover, they found that TSE was quite stable among experienced teachers, with autocorrelations of up to .80, thus further TEACHER SELF-EFFICACY, INSTRUCTIONAL QUALITY AND STUDENT MOTIVATIONAL BELIEFS 25 complicating the determination of causal inferences (see e.g., Antonakis, Bendahan, Jacquart, & Lalive (2014) for further discussions).…”
Section: Limitations and Future Directionsmentioning
confidence: 74%
“…Therefore, our findings contribute to general motivation research, which has emphasized the situated character of human motivation (Reeve, 2016), and extends the findings to professional domains such as teaching. In previous studies, self-efficacy remained rather stable across lessons, which could be due to the longer time period investigated (Holzberger et al, 2013;Praetorius et al, 2017). Therefore, the measures applied in those studies were more related to general teaching self-efficacy and not as context-sensitive as our measures which directly asked about the self-efficacy in the lessons during the specific documented week.…”
Section: Discussionmentioning
confidence: 78%
“…This assumption is in line with recent motivational theories (Eccles, 2005;Hidi & Harackiewicz, 2000), which highlight that motivational beliefs depend on distinct aspects of the task to be accomplished and contextual aspects determining the distinct tasks. Therefore, teacher motivation might vary across lessons (Holzberger, Philipp, & Kunter, 2013;Praetorius et al, 2017).…”
Section: Variability Of Technology Integration and Motivation Across Lessonsmentioning
confidence: 99%